Isolation and identification of Yersinia pseudotuberculosis from rodent species Tatera indica - TUTEJA, URMIL; JAIN, REENA; BATRA, H V (The Indian Journal of Animal Sciences, 2014)
issue specimens of Tatera indica rodents examined during plague surveillance in the Deccan plateau yielded 4 isolates of Yersinia pseudotuberculosis confirmed on the basis of conventional biochemical testing and by bacteriophage lysis test. These isolates when subjected to SDS-PAGE analysis could be easily distinguished from other yersiniae and non-yersinae species of family enterobacteriacae. Two thick prominent bands at 14-16kDa and 24-26kDa regions were characteristic identification markers for Y. pseudotuberculosis.